Report on the refugees bill 2019 annexes - National Assembly (My University, 2020)
The Refugees Bill, 2019 (National Assembly Bills No. 62) underwent First Reading on 10111 September, 2019. Thereafter, the Bill was committed to the Departmental Committee on Justice and Legal Affairs for review and report to the House pursuant to the provisions of Standing Order 216(5)(c). Pursuant to the provisions of Article 118 of the Constitution of Kenya and Standing Order 127(3) of the National Assembly Standing Orders, the Committee through local daily newspapers of 9t1-1 October, 2019 published an advertisement inviting the public to submit memoranda on the Bill and indeed received memoranda. The Committee through the same advertisement notified the public about its conducting of public hearings on the Bill in selected counties. The public hearings took place in Nairobi, Mombasa, Nakuru, Uasin Gishu, Garissa and Turkana during which members of the public either individually or representing institutions and organizations made oral presentations and or submitted written memoranda which the Committee took into account while reviewing the Bill. The report contains public views on the Bill, public participation process, observations and recommendations. The report also contains analysis of public submissions which the Committee found relevant and useful in review of the Bill as well as written memoranda and lists of members of the public who attended the public hearings. May I take this opportunity to thank and commend Committee Members for devotion and commitment to duty, the Speaker and Clerk of the National Assembly for providing leadership and direction and finally the Committee secretariat for exemplary performance in the provision of technical and logistical support. Indeed, their efforts were critical in the consideration of the Bill and production of this report. On behalf of the Departmental Committee on Administration and National Security and pursuant to the provisions of Standing Order 199 (6), it's my pleasant privilege and duty to present to the House a report of the Committee on the Refugees Bill, 2019 (National Assembly Bills No. 62)
Keywords: refugees bill